Generation of Nppa‐tagBFP reporter knock‐in mouse line for studying cardiac chamber specification. Issue 6 (28th March 2019) - Zhang, Zhentao; Zhang, Qinkun; Lal, Hind; Nam, Young‐Jae
Summary: Nppa is a cardiac hormone which plays critical roles in regulating salt–water balance. Its expression is restricted to the atria of the healthy post‐natal heart. During heart development, spatio‐temporal expression of Nppa is dynamically changed within the heart and becomes restricted to the atria upon birth. In contrast to its atrial specific expression after birth, Nppa is re‐expressed in the adult ventricles in response to cardiac hypertrophy. To study cardiac chamber specification during development and pathological cardiac remodeling during heart disease, we generated a novel Nppa reporter mouse line by knocking‐in a tagBFP reporter cassette into 3′‐UTR of the Nppa gene without disrupting the endogenous gene. Our results demonstrated dynamic tagBFP expression in the developing heart, recapitulating the spatiotemporal expression pattern of endogenous Nppa. We also found that Nppa‐tagBFP is induced in the ventricle during pathological remodeling. Taken together, Nppa‐tagBFP reporter knock‐in mouse model described in this article will serve as a valuable tool to study cardiac chamber specification during development as well as pathological cardiac remodeling.